WOMEN’S IDEOLOGY IN THE NOVEL HATI SUHITA BY KHILMA ANIS DEMINIST HEGEMONY STUDY - Diastuti, Indah Mei; Supratno, Haris; Suyatno; Suhartono (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Women’s ideology is the complexity of views, ideas and ideals that women have which is a reflection of their way of thinking to achieve the desired goals. This research aim for reveals women’s ideology in the novel Hati Suhita through the frame of studying the hegemony of feminism. The novel discussed is the novel Hati Suhita by Ning Khilma Anis. The method used in this research in qualitative. The data source in this research is the novel Hati Suhita by Khilma Anis. The approach in this research is through the hegemony of feminism. The data in this research is in the form of data description findings in Suhita’s novel Hati Suhita that are relevant between objects and the reality around them. The data collection technique used is documentary study. The analysis technique used is the hermeneutic model. The result obtained show that the study of feminist hegemony in Suhita’s novel Hati can see that the women in this story face many challenges. In this context, women Suhita’s heart can be considered as an ideology that is different from the ideology of men. Women are expected to be servants, while men are given great power and authority in traditional society. The womanin this story show that they are capable of being outside the roles prescribed by society and that they have different abilities and personalities.